Análisis de los factores que impiden que la playita El Salto del cantón Babahoyo no se desarrolle turísticamente - León Alvarado, Jomely Estefani (2020)
This research work was carried out in the El Salto parish of the canton of Babahoyo, specifically in its natural resource such as the freshwater river, where the local community uses this space as a recreation area and spa in carnival time and day Of wise men, nationwide, freshwater spas develop tourism, however, the jump beach does not succeed in becoming a tourist site for this reason this case study was conducted to determine the factors that affect the beach jump does not develop tourism, in order to identify these factors that prevent this development two methodology was carried out, a survey and through an observation instrument it was possible to demonstrate the absence of tourist services, garbage containers, cultural resources and gastronomic stops, same that affects the tourist influx in the parish El Salto of the canton of Baba hole. In this place the problem of non-existence of resources that contribute to the development of the freshwater spa has been identified and that this affects tourism in the El Salto beach, which is demonstrated by the collection of the 130 surveys conducted online that the beach resort Freshwater does not have the full tourist services to meet the needs of tourists visiting the place.